Representation of 'Muslim' in Jakarta Governor Election 2017 in The Washington Post: A Critical Discourse Analysis - Titania Sari; Ai Yeni Yuliyanti; Ponia Mega Septiana (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2022)
This research explores how The Washington Post online newspaper represents Muslims and non-Muslims in the Jakarta governor election in 2017. The researcher obtained the data from the article in The Washington Post on May 5, 2017. This qualitative research used Norman Fairclough's Critical Discourse Analysis Theory (2003) approaches in the textual and social practice analysis dimensions. The textual analysis dimension is analyzed using Halliday's transitivity theory (2014), focusing on process type at representational meanings. The researcher collects, classifies, and explores the data. The findings show that the most apparent in the sentences of articles are mental and verbal processes, and there is no behavioral process. The result shows that the Washington Post represents Muslims primarily negatively. Muslims is represented as conflict maker and a winner in the event because of the non-Muslim candidate's offense. The Muslim society is represented as having conflict, and hard-line Muslim communities want to apply Islamic law to the Indonesian government.